Incidence of successful voiding and predictors of early voiding dysfunction after retropubic sling. Issue 8 (August 2016) - Barr, Susan; Thomas, Amanda; Potter, Shannon; Melick, Clifford; Gavard, Jeffrey; McLennan, Mary
Abstract Introduction and hypothesis There is a paucity of literature on resumption of normal voiding predictors after synthetic retropubic sling insertion and lack of a standardized method of determination. Our goals were to determine the incidence of a successful voiding trial; whether clinical, operative, or urodynamic variables predict discharge with a catheter; and incidence of later retention in those who were initially successful. Methods We performed an internal-review-board (IRB)-approved retrospective chart review of 229 consecutive patients who underwent retropubic sling (TVT, Boston Scientific, Natick, MA, USA)) from 2001 to 2010. Exclusions were concomitant surgery or cystotomy at the time of retropubic sling insertion. All participants underwent a voiding trial in recovery consisting of 300 cc sterile-water retrograde fill and were discharged home without a catheter after single void of at least 200 cc following catheter removal. Results Of 170 patients, 136 (80 %) passed the voiding trial the same day, with 165 (97 %) passing within 1 day. Factors associated with delayed voiding were age ≥65 years (p < 0.05), presence of Valsalva voiding (p < 0.01), lower body mass index (BMI) (p < 0.05), and higher gravidity (p < 0.05) and parity (p < 0.01). Age ≥65 years [adjusted odds ratio (aOR) 3.72, 95 % confidence interval (CI) 1.40–9.90, p < 0.01] and Valsalva voiding (aOR 3.89, 95 % CI 1.56–9.69, p < 0.01) remained significant independent predictors in multivariate analysis. Conclusions The majority of patients with retropubic sling can be safely discharged home the same day without a catheter after retrograde fill. Women >65 years or Valsalva voiders had nearly four times the odds of being discharged with a catheter. Summary Most patients resume normal voiding within 24 h after retropubic sling insertion, but >65 years and Valsalva voiding are risk factors for voiding inability at discharge.